NEW DEVELOPMENTS AND REFORM PROPOSALS OF THE MACROECONOMIC IMBALANCE PROCEDURE - Daniel Stavarek (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The European Union (EU) has had a five-year experience with the Macroeconomic Imbalance Procedure (MIP) that was introduced by the European Commission in December 2011 as a response to accumulation of huge imbalances with the EU and the euro area. This paper evaluates results of the MIP and aims to examine what kind of imbalances have been revealed by the MIP, evaluate the current settings of the MIP and propose reforms that would enhance functioning and applicability of the MIP in practice. Based on results published in Alert Mechanism Reports and In-Depth Reviews and evaluation of the yearly cycle of the MIP, we propose several reforms and changes in the MIP and the scoreboard of indicators in particular. We bring forward a concept of relative thresholds that reflect economic development much better than currently applied absolute thresholds. Moreover, we recommend modification of some of the indicators involved in the MIP and introduction of maximally three flagship indicators that would receive special attention in assessment of the risk stemming from macroeconomic imbalances.